Pengaruh Kemampuan Pedagogical Knowledge dan Subject Matter Knowledge Terhadap Kemampuan Mengajar Mahasiswa PPL Program Studi Pendidikan Fisika Universitas Flores - Adrianus Nasar; Melkyanus Bili Umbu Kaleka (Program Studi Pendidikan Fisika STKIP Nurul Huda, 2019)
This study aims to determine the effect of pedagogical knowledge and subject matter knowledge on the teaching ability of students of the Physics Education of Universitas Flores. The method used is survey research using a quantitative approach. The population is students, and a sample of 30 students is obtained by systematic sampling. The research data were analyzed statistically using multiple linear regression equations. The results showed that there was a positive effect between pedagogical knowledge skills and the ability of subject matter knowledge with the teaching ability students of Physics Education of Universitas Flores. The results showed that there was a positive effect of pedagogical knowledge and the ability to subject matter knowledge with the teaching abilities of School Teaching Practice of students.